UPAYA PENINGKATAN MOTIVASI BELAJAR PKN SISWA KELAS IV SD NEGERI 011 PAGARAN TAPAH DARUSSALAM MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY - Misnawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low motivation to learn Civics among fourth-grade students at SD Negeri 006 Pagaran Tapah Darussalam. The purpose of this study was to determine whether the learning motivation of fourth-grade students at SD Negeri 011 Pagaran Tapah Darussalam could be improved through the implementation of the Two Stay Two Stray cooperative learning model, which was carried out over a period of one month. The subjects of this study were fourth-grade students of SD Negeri 011 Pagaran Tapah Darussalam in the 2016–2017 academic year, totaling six students consisting of four boys and two girls. This study employed a classroom action research design. The research instruments included performance instruments and data collection tools in the form of teacher and student activity observation sheets. Based on the analysis and discussion presented in Chapter IV, it can be concluded that the application of the Two Stay Two Stray cooperative learning model was effective in increasing students’ motivation to learn Civics in the fourth grade at SD Negeri 011 Pagaran Tapah Darussalam. This improvement can be observed from changes in students’ motivation between Cycle I and Cycle II. In Cycle I, students’ motivation reached a score of 15 with an average motivation level of 41.7, which was categorized as low. In Cycle II, students’ motivation increased significantly to a score of 31 with an average motivation level of 86.1, categorized as very high. Based on the predetermined performance indicators, this research was considered successful because student motivation exceeded the minimum achievement criterion of 75% of all students.